A Pre-Liminary Study : Potential Economic Tailing Exploring by Geophysical Logging Method in Bangka - Nomensen Ricardo; Satyogroho Dhian Amertho; Cindra Putra Azana (PERHAPI, 2022)
In Bangka-Belitung Provinces, PT Timah TBK hold 120 mining concession permit (IUP) which is about 428,378.98 Ha. Mining activities begun significantly at colonial era (before 1945) and continued until recent day. The massive mining activities produced abounded remains tailing (mineral processing residue). The selective mining on tin ore caused the other potential economic mineral were neglected. Hence, this study is aimed to reorganize and manage the potential economic mineral at tailing area that’s distributed in mining consesion permit of PT Timah TBK . Study area are located in Air Rirung (Bangka Regency) and Air Nudur (South Bangka). Both are comprised of tailing material (loose sediment). Geophysical logging tools (GammaRay and Density Log), elemental analysis (using XRF handheld portable) and grain size analysis (sieving) are applied to identify the interest tailing area. Low density and high Gammaray indicate dominantly clay content in coarse sand, while high density and low Gammaray indicate little or no clay content in coarse sand. Furthermore, GammaRay detected Thorium (Th) and Uranium (U) content that come from monazite mineral. The heavy mineral (ilmenite) is distributed on bottom of each layering (stage). By element to element correlation, stannum (Sn) shows good correlation to Fe-Ti and Ce-Y-La-Th-U. Comparing to Gammaray, at fraction -#200 Th and Y shows good positive corelation to GR log, while at fraction +#200 Th and Y shows good negative correlation. In spatial distribution, the heavy mineral and coarse grain are deposited near from the source while the light mineral and fine grain relatively are deposited faraway from the source. Using IDW Method, the potential REE in monazite mineral are estimated of 8.0 tonnes in Air Rirung and 1.6 tonnes in Air Nudur.